Photobiocatalysis in Continuous Flow - Chanquia, Santiago Nahuel; Valotta, Alessia; Gruber-Woelfler, Heidrun; Kara, Selin (Frontiers in Catalysis, 2022)
In the last years, there were two fields that experienced an astonishing growth within the biocatalysis community: photobiocatalysis and applications of flow technology to catalytic processes. Therefore, it is not a surprise that the combination of these two research areas also gave place to several recent interesting articles. However, to the best of our knowledge, no review article covering these advances was published so far. Within this review, we present recent and very recent developments in the field of photobiocatalysis in continuous flow, we discuss several different practical applications and features of state-of-the art photobioreactors and lastly, we present some future perspectives in the field.